Going home - Steel, Danielle (New York : Pocket Books, 1973)
In the sun swept beauty of San Francisco, Gillian Forrester is filled with the joy of a love that will surely last. But a painful betrayal forces her to flee to New York and begin a new life. There she discovers an exciting new career and a deep, enveloping passion$1! =(Bonly to have her newfound happiness shaken to its core. Now Gillian must choose between her future and her past, and find in the deepest desires of her heart the one way, the only way of Going Home.s
Keywords: Man-woman relationships -- Fiction; Love stories